2011
DOI: 10.1038/embor.2011.235
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2 associates with Ras effector NORE1 to induce the degradation of oncoprotein HIPK1

Abstract: The Ras effector NORE1 is frequently silenced in primary adenocarcinomas, although the significance of this silencing for tumorigenesis is unclear. Here we show that NORE1 induces polyubiquitination and proteasomal degradation of oncoprotein HIPK1 by facilitating its interaction with the Mdm2 E3 ubiquitin ligase. Endogenous HIPK1 is stabilized in Nore1-deficient mouse embryonic fibroblasts, and depletion of HIPK1 in NORE1-silenced lung adenocarcinoma cells inhibits anchorage-independent cell growth and tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Recent studies have shown that the ubiquitin ligase mdm2, a negative regulator of Rb that contributes to tumorigenesis in part by destabilizing Rb (67), can be found in an endogenous complex with PP1A (68), although the effects of mdm2 on PP1A stability have not been elucidated. Interestingly, NORE1A has been shown to regulate the degradation of specific mdm2 targets (69). Therefore, NORE1A could be regulating PP1A stability through its interaction with mdm2, potentially by antagonizing the ubiquitination/degradation properties of mdm2.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the ubiquitin ligase mdm2, a negative regulator of Rb that contributes to tumorigenesis in part by destabilizing Rb (67), can be found in an endogenous complex with PP1A (68), although the effects of mdm2 on PP1A stability have not been elucidated. Interestingly, NORE1A has been shown to regulate the degradation of specific mdm2 targets (69). Therefore, NORE1A could be regulating PP1A stability through its interaction with mdm2, potentially by antagonizing the ubiquitination/degradation properties of mdm2.…”
Section: Discussionmentioning
confidence: 99%
“…NORE1A forms a complex with MDM2, the principal regulator of p53 [43, 143] and regulates the stability of MDM2 in a Ras-dependent manner [144]. The mechanism appears to involve poly-ubiquitination mediated by the NORE1A/β-TrCP complex, in contrast to RASSF1A, which promotes MDM2 self-ubiquitination [44].…”
Section: Nore1a (Rassf5)mentioning
confidence: 99%
“…Required for apoptosis and growth inhibition [8] Inhibits MST2 activity [93] Modulates the MAP kinase signal downstream of the Ras signal [77] K-Ras [8] ST1, MST2 [177] MST1 [75] Not available 5A (Nore1A) 1q32 47.1 kDa Suppresses tumour growth via apoptosis induction or cell cycle delay [7,82] Regulates microtubule formation [182] Induces degradation of HIPK1 oncoprotein [183] Required for the TNFa mediated apoptosis and full activation of MST1 [80] Ras, Carma1 [182,184] MST1 [43,177] MST2 [177] tubulin, Aurora A [182] Mdm2 [183] Itch [185] Yes [80] resistant to TNFa-induced apoptosis, fail to activate Mst1 in vivo 5C (Nore1B, RAPL) 1q32 30.4 kDa…”
Section: Kdamentioning
confidence: 99%